A new sandstone-dwelling leaf-toed gecko (Gekkonidae: Dixonius hinchangsi) from Khon Kaen Province, northeastern Thailand - Pauwels, Olivier S. G.; Das, Sunandan; Kunya, Kirati; Sumontha, Montri; Donbundit, Nattasuda; Pauwels, Thomas P. C.; Sonet, Gontran; Brecko, Jonathan; Meesook, Worawitoo (Zootaxa, 2025)
We describe Dixonius hinchangsi sp. nov. from a sandstone area near Hin Chang Si, Khon Kaen Province, northeastern Thailand. The new species differs from all currently recognized Dixonius by the following combination of morphological characters and pattern: maximal known snout-vent length of 50.1 mm, 12 longitudinal rows of dorsal tubercles; 30 to 34 paravertebral tubercles; 23 to 27 longitudinal rows of ventral scales across the abdomen; six to eight precloacal pores in males, no pores in females; no canthal stripe; strongly barred lips; and a spotted to uniform dorsal pattern in males and females. We provide a cranial osteological description and a phylogenetic analysis of the new species. This discovery brings the number of recognized Dixonius species to 19, among them nine species endemic to Thailand.